Accelerated Failure Time Model for Determination of Effectiveness of Antiretroviral Therapy at General Hospital Adikpo, Benue State, Nigeria - T., Mom T.; A., Ikughur J.; F., Udoumoh E. (Asian Journal of Science, Technology, Engineering, and Art, 2025)
The introduction of antiretroviral therapy (ART) has markedly improved the clinical outcomes of individuals living with HIV, transforming the infection from a fatal illness to a manageable chronic condition. Central to HIV management is the CD4 count, a critical biomarker that reflects immune system status and informs clinical decisions regarding ART initiation and the management of opportunistic infections. Reaching a CD4 threshold of ≥500 cells/mm³ is widely considered a key indicator of immune reconstitution and long-term treatment success. However, there remains limited guidance for patients and clinicians on the expected timeline or probability of reaching this milestone, highlighting the need for robust statistical models to support evidence-based treatment planning. This study employed a retrospective cohort design using data from 400 HIV-positive patients who initiated ART at General Hospital Adikpo, Benue State, Nigeria, between 2012 and 2022. Inclusion criteria required that patients begin treatment with a CD4 count <500 cells/mm³. Over the study period, 54% of patients (216) achieved a CD4 count ≥500 cells/mm³, while 46% (184) did not. The Anderson-Darling (test statistic: 0.3660) and Chi-square (test statistic: 12.73) tests confirmed that the lognormal accelerated failure time (AFT) model was an appropriate fit for estimating the time to immune recovery. The analysis revealed that the rate of CD4 improvement was highest in the initial years following ART initiation, with diminishing returns over time. The median time to achieve the CD4 threshold was five years. Key predictors of successful immune reconstitution included baseline CD4 count, patient age, and tuberculosis (TB) status (p < 0.05). These findings reinforce the critical importance of early HIV detection, timely initiation of ART, and integrated TB management in improving long-term immunological outcomes.